Fatal toxoplasmosis in a southern muriqui (Brachyteles arachnoides) from São Paulo state, Brazil: Pathological, immunohistochemical, and molecular characterization. Issue 2 (29th November 2017) - Santos, Stéfanie Vanessa; Pena, Hilda F.J.; Talebi, Mauricio G.; Teixeira, Rodrigo H.F.; Kanamura, Cristina T.; Diaz‐Delgado, Josué; Gennari, Solange M.; Catão‐Dias, José Luiz
Abstract: We report the pathological, immunohistochemical, and molecular features of fatal acute systemic toxoplasmosis in an adult, female, free‐living southern muriqui ( Brachyteles arachnoides ) from São Paulo state, Brazil. PCR‐RFLP genotyping analysis identified the #21 genotype of Toxoplasma gondii . This represents the first report of acute toxoplasmosis involving this genotype in humans and animals.